2020
DOI: 10.1002/ijc.32858
|View full text |Cite
|
Sign up to set email alerts
|

The association between fasting blood glucose trajectory and cancer risk in Chinese population without diabetes

Abstract: To examine the associations between fasting blood glucose (FBG) trajectories, the changes in FBG over time and the risk of cancer, particularly for gastrointestinal cancer, we enrolled 69,742 participants without diabetes from the Kailuan cohort. FBG trajectories (2006–2010) were modeled by group‐based trajectory modeling, and five trajectories were identified: low‐increasing (n = 6,275), moderate‐stable (n = 44,120), moderate‐increasing (n = 10,149), elevated‐decreasing (n = 5,244) and elevated‐stable (n = 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…36 A Chinese study performed trajectory analysis using longitudinal FBG data and found that the risk of GI cancer was significantly higher in the group with persistent IFG. 37 These findings support the proposal that both the extent and duration of hyperglycemia are essential factors for cancer development. In our study, more than half of the study population had changes in their glycemic status over 4 years.…”
Section: Discussionsupporting
confidence: 75%
“…36 A Chinese study performed trajectory analysis using longitudinal FBG data and found that the risk of GI cancer was significantly higher in the group with persistent IFG. 37 These findings support the proposal that both the extent and duration of hyperglycemia are essential factors for cancer development. In our study, more than half of the study population had changes in their glycemic status over 4 years.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study suggested an association between diabetes and risk of gastric cancer only at least 5 years after the diabetes diagnosis [ 7 ]. Another study found that only long-lastingly elevated serum glucose levels (but not other trajectory patterns) were associated with an increased risk of gastrointestinal cancer (HR 1.66, 95% CI 1.22–2.26) [ 45 ]. Another potential link between high HbA1c levels and gastric carcinogenesis might be the treatment for long-term poor glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Although many patients have multiple episodes of abnormal FBG during hospitalization, it remains unclear whether a patient should be diagnosed with type 2 diabetes, considering the possibility of stress hyperglycemia and the effect of medications on blood glucose. In a prospective cohort study, discrete FBG trajectories were significantly associated with subsequent risk of myocardial infarction and cancer in individuals without diabetes ( 24 , 25 ). In addition to diabetes, changes in FBG may also play a key role in the development of other diseases.…”
Section: Discussionmentioning
confidence: 99%